2008
DOI: 10.1126/science.1163148
|View full text |Cite
|
Sign up to set email alerts
|

The Extreme Kuiper Belt Binary 2001 QW 322

Abstract: The study of binary Kuiper Belt objects helps to probe the dynamic conditions present during planet formation in the solar system. We report on the mutual-orbit determination of 2001 QW322, a Kuiper Belt binary with a very large separation whose properties challenge binary-formation and -evolution theories. Six years of tracking indicate that the binary's mutual-orbit period is approximately 25 to 30 years, that the orbit pole is retrograde and inclined 50 degrees to 62 degrees from the ecliptic plane, and, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 10 publications
0
57
1
Order By: Relevance
“…The black curve is obtained after thermal processing of bodies with 65% ice formed with v coll = v esc /2. Measured densities for dynamically cold classical disk objects (black, gray) are taken from Petit et al (2008), Vilenius et al (2012Vilenius et al ( , 2014, and Carry (2012) based on Grundy et al (2009Grundy et al ( , 2013. Densities for dynamically hot classical disk objects, SD objects, and Centaurs (red) are taken from Blum & Wurm 2008) can be added to the gravitational pressure.…”
Section: The Cold Classical Ekbmentioning
confidence: 99%
See 1 more Smart Citation
“…The black curve is obtained after thermal processing of bodies with 65% ice formed with v coll = v esc /2. Measured densities for dynamically cold classical disk objects (black, gray) are taken from Petit et al (2008), Vilenius et al (2012Vilenius et al ( , 2014, and Carry (2012) based on Grundy et al (2009Grundy et al ( , 2013. Densities for dynamically hot classical disk objects, SD objects, and Centaurs (red) are taken from Blum & Wurm 2008) can be added to the gravitational pressure.…”
Section: The Cold Classical Ekbmentioning
confidence: 99%
“…The targets in black were observed with Herschel by Vilenius et al (2012Vilenius et al ( , 2014 and have radiometrically determined sizes and geometric albedos (except 2001 QW 322 for which Petit et al 2008 assumed p V = 0.16). For the targets in gray Grundy et al (2009Grundy et al ( , 2013 assumed ranges for ρ bulk and p V to constrain diameters.…”
Section: The Cold Classical Ekbmentioning
confidence: 99%
“…For example, according to Goldreich et al (2002), collisionless gravitational interactions are more efficient in forming the observed, widely separated binaries in the primordial KB than (3). Also, model (4) leads to binary eccentricities e 0.8 and very large semimajor axes, while observations of binary KBOs indicate moderate eccentricities and semimajor axes that are only a few percent of the Hill radius (Noll et al 2008a;Grundy et al 2009), except for 1998 WW 31 with e = 0.82 (Veillet et al 2002) and 2001 QW 322 with a = 120,000 km (Petit et al 2008). Schlichting & Sari (2008a) estimated that chaotic capture in (5) should be less common than direct capture in (1) or (2).…”
Section: Binary Formation In Hierarchical Coagulationmentioning
confidence: 99%
“…For example, typical high-eccentricity BMPs produced in some scenarios such as the expected e > 0.8 in the exchange scenario of Funato et al (2004), or 0.2 e 0.8 in the chaos assisted capture scenario (Lee et al 2007), could be observed with very low eccentricities, either due to the random phase in which they are observed during their Kozai cycle or due to their KCTF evolution which would have circularized their orbit (e.g., Figure 2). Recently, (and after the initial presentation of this manuscript), Petit et al (2008) have reported on the peculiar orbit of the Kuiper Belt binary 2001 QW 322 , with very large SMA but relatively small eccentricity. Such orbit is difficult to explain through previously suggested BMPs formation scenarios, since a binary with such wide SMA is likely to be produced through the exchange scenario, which would typically produce a highly eccentric binary (Funato et al 2004).…”
Section: Kctf Observational Signature and Bmps Formations Scenariomentioning
confidence: 99%